1992
DOI: 10.1530/jrf.0.0950791
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role for a uterine renin-angiotensin system in decidualization in rats

Abstract: Experiments were performed in vivo and in vitro to determine the effects of enalaprilat, a specific inhibitor of angiotensin-converting enzyme, on various aspects of the decidual cell reaction in rats. Ovariectomized, adult female rats were sensitized for the decidual cell reaction with steroid treatments. For in vivo experiments, intrauterine infusions of enalaprilat alone, and in combination with angiotensin II and prostaglandin E2 (PGE2), were initiated on the day of uterine sensitivity. Enalaprilat inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
4
21
1
1
Order By: Relevance
“…Several classes of potent and specific nonpeptide inhibitors have been synthesized in an effort to produce active ACE inhibitors that could be useful as antihypertensive agents (34). Captopril is thought to bind the active site of ACE in a manner analogous to endogenous substrates, and has been widely used in experiments designed to define the biological function of ACE (35)(36)(37)(38). The addition of captopril to the perfusate did not inhibit hCG-induced ovulation, despite significant reductions in both the intrafollicular Ang II content and the secretion rate ofAng II in ovaries perfused with hCG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several classes of potent and specific nonpeptide inhibitors have been synthesized in an effort to produce active ACE inhibitors that could be useful as antihypertensive agents (34). Captopril is thought to bind the active site of ACE in a manner analogous to endogenous substrates, and has been widely used in experiments designed to define the biological function of ACE (35)(36)(37)(38). The addition of captopril to the perfusate did not inhibit hCG-induced ovulation, despite significant reductions in both the intrafollicular Ang II content and the secretion rate ofAng II in ovaries perfused with hCG.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the treatment ofcultured endometrial decidual cells with enalaprilat, an another ACE inhibitor, inhibits the production of PGE2 in a dose-dependent manner, but that the concurrent administration of Ang II does not reverse the inhibitory effect of enalaprilat (38) (45)(46)(47). Our previous study also revealed that bradykinin significantly stimulated the production of PG by perfused rabbit ovaries (40).…”
Section: Resultsmentioning
confidence: 99%
“…The synthase localized to granulosa cell surface membranes has been shown to be induced by hCG [30]. Angiotensin II is known to stimulate PG synthesis in both central and peripheral tissues by the activation of specific phospholipases [27,[31][32][33]. The activation of phospholipase C results in the production of inositol 1,4,5-triphosphate, which could release arachidonic acid for PG synthesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Tenascin is expressed in the smooth muscle layers of arteries, especially during tissue remodelling processes, and is thought to be stimulated by an increase in mechanical stress or by angiotensin II [30,31]. Using enalaprilat (Merck Frosst Canada Inc., Dorval, PQ, Canada), a specific inhibitor of angiotensin-converting enzyme, Squires and Kennedy [32] provided evidence of a requirement for angiotensin II locally during the decidual cell reaction in rats.…”
Section: Discussionmentioning
confidence: 99%